Reduced helminth burden increases allergen skin sensitization but not clinical allergy: a randomized, double-blind, placebo-controlled trial in Vietnam. - Flohr, C; Tuyen, L; Quinnell, R; Lewis, S; Minh, T; Campbell, J; Simmons, C; Telford, G; Brown, A; Hien, T; Farrar, J; Williams, H; et al. (2010)
BACKGROUND: Observational evidence suggests that infection with helminths protects against allergic disease and allergen skin sensitization. It is postulated that such effects are mediated by helminth-induced cytokine responses, in particular IL-10. OBJECTIVE: We tested this hypothesis in a rural area of central Vietnam where hookworm infection is endemic. METHODS: One thousand five hundred and sixty-six schoolchildren aged 6-17 were randomly allocated to receive either anti-helminthic therapy or a placebo at 0, 3, 6, and 9 months. We compared changes in the prevalence of exercise-induced bronchoconstriction, allergen skin sensitization, flexural eczema on skin examination, questionnaire-reported allergic disease (wheeze and rhinitis symptoms), and immunological parameters (hookworm-induced IFN-gamma, IL-5, IL-10) between 0 and 12 months. RESULTS: One thousand four hundred and eighty-seven children (95% of these randomized) completed the study. The most common helminth infections were hookworm (65%) and Ascaris lumbricoides (7%). There was no effect of the therapy on the primary outcome, exercise-induced bronchoconstriction (within-participant mean percent fall in peak flow from baseline after anti-helminthic treatment 2.25 (SD 7.3) vs. placebo 2.19 (SD 7.8, P=0.9), or on the prevalence of questionnaire-reported wheeze [adjusted odds ratio (OR)=1.16, 95% confidence interval (CI) 0.35-3.82, P=0.8] and rhinitis (adjusted OR=1.39, 0.89-2.15, P=0.1), or flexural dermatitis on skin examination (adjusted OR=1.15, 0.39-3.45, P=0.8). However, anti-helminthic therapy was associated with a significantly higher allergen skin sensitization risk (adjusted OR=1.31, 1.02-1.67, P=0.03). This effect was particularly strong for children infected with A. lumbricoides at baseline (adjusted OR=4.90, 1.48-16.19, P=0.009). Allergen skin sensitization was inversely related to hookworm-specific IL-10 at baseline (adjusted OR=0.76, 0.59-0.99, P=0.04). No cytokine tested, including IL-10, changed significantly after the anti-helminthic therapy compared with the placebo. CONCLUSION: A significant reduction in worm burden over a 12-month period in helminth-infected children increases the risk of allergen skin sensitization but not of clinical allergic disease. The effect on skin sensitization could not be fully explained by any of the immunological parameters tested.